Firm ownership and rent sharing - Monteiro, Natália (2010)
We analyse - theoretically and empirically - how private versus public ownership of firms affects the degree of rent sharing between firms and their workers. Using a particularly rich linked employer-employee dataset from Portugal, covering a large number of corporate ownership changes across a wide spectrum of economic sectors over more than 20 years, we find a positive relationship between private ownership and rent sharing. Based on our theoretical analysis, this result cannot be explained by private firms being more profit oriented than public ones. However, the result is consistent with privatisation leading to less job security, implying stronger efficiency wage effects.